2017
DOI: 10.1016/j.jallcom.2017.03.222
|View full text |Cite
|
Sign up to set email alerts
|

Si/SiC optical coatings for C/SiC composites via gel-casting and gas silicon infiltration: Effects of carbon black content

Abstract: The dense Si/SiC coatings are fabricated by means of gel-casting (GC) and gas silicon infiltration (GSI) for the first time, using carbon black and α-SiC as raw materials. The influences of the carbon black content on the properties of the coating samples have been investigated. Resultsshow that, with the increase of the carbon black content, the viscosity of the slurry increase dramatically, the density and the porosity are closer to theoretical results, leading to the higher density after GSI. And the β-SiC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…In this study, the mass ratios of Si/α-SiC and Si/β-SiC ( X Si / X α‑SiC and X Si / X β‑SiC ) were calculated using the K value method’s eq (Supporting Information S3.2). , In Figure S8, the variation trend curves of X Si(111) / X α‑SiC(101) and X Si(111) / X β‑SiC (311) were obtained in accordance with eq during elevated temperature. The variation trend curves revealed that X j / X i was greater at 1100 and 1200 °C than at other temperatures.…”
Section: Resultssupporting
confidence: 58%
“…In this study, the mass ratios of Si/α-SiC and Si/β-SiC ( X Si / X α‑SiC and X Si / X β‑SiC ) were calculated using the K value method’s eq (Supporting Information S3.2). , In Figure S8, the variation trend curves of X Si(111) / X α‑SiC(101) and X Si(111) / X β‑SiC (311) were obtained in accordance with eq during elevated temperature. The variation trend curves revealed that X j / X i was greater at 1100 and 1200 °C than at other temperatures.…”
Section: Resultssupporting
confidence: 58%
“…Three dimensional, five-directional braided, carbon fabrics (volume fraction ~50%) provided by the Composites Institute of Tianjing Technology University (China) were used to prepare C/C preforms through Chemical Vapor Infiltration (CVI) at 960°C, with propylene and argon used as precursor and carrier diluting gases respectively. Preforms with a density of about 1.40 g/cm 3 (after 130 hours of CVI) were used to fabricate C/C-SiC composites by Gaseous Silicon Infiltration [34] at 1700°C. Preforms with density of about 1.08 g/cm 3 (after 35 hours of CVI) were used to fabricate composites by the Precursor Infiltration and Pyrolysis method [35] at 1200°C.…”
Section: Materials Preparationmentioning
confidence: 99%
“…The needled short-cut felt was infiltrated by CVI for 60 h to a density of 1.10 g/cm 3 . The C/C-SiC composites were prepared from the three preforms by gaseous silicon infiltration (GSI) [31] at 1700°C for 2 h, and achieved final densities in composites ①, ② and ③ of 2.37 g/cm 3 , 2.16 g/cm 3 and 2.61 g/cm 3 respectively ( Table 2).…”
Section: Materials and Characterization Methodsmentioning
confidence: 99%